Qualitative Research: Hermeneutical Phenomenological Method - Fuster Guillen, Doris Elida (2019)
This article shows fundamental notions of one of the qualitative research methods, we refer to the hermeneutical phenomenology based on the theories of Van Manen, Raquel Ayala and Miguel Martínez. This approach leads to the description and interpretation of the essence of lived experiences, recognizes the meaning and importance in pedagogy, psychology and sociology according to the experience collected. This method constitutes rigorous and consisted processes of the ethical dimensions of the daily experience, which are difficult to be accessed by other usual research methods. In this contribution, we present some methodological notions focused on the principles of phenomenology and its phases: previous stage or clarification of budgets, collecting the experience lived, reflecting on the lived experience or structural stage and, finally, writing-reflecting on the lived experience evidenced in individual and group physiognomy or also called phenomenological text.